OXYGEN ISOTOPE EXCHANGE AND DISEQUILIBRIUM BETWEEN CALCITE AND TREMOLITE IN THE ABSENCE AND PRESENCE OF AN EXPERIMENTAL C-O-H FLUID - Zheng Y.F.; Satir M.; Metz P. (My University, 2004)
Oxygen isotope exchange between minerals during metamorphism can occur in either the presence or the absence of aqueous fluids. Oxygen isotope partitioning among minerals and fluid is governed by both chemical and isotopic equilibria during these processes, which progress by intragranular and intergranular diffusion as well as by surface reactions. We have carried out isotope exchange experiments in two- and three-phase systems, respectively, between calcite and tremolite at high temperatures and pressures. The two-phase system experiments were conducted without fluid either at 1 GPa and 680 °C for 7 days or at 500 MPa and 560 °C for 20 days. Extrapolated equilibrium fractionations between calcite and tremolite are significantly lower than existing empirical estimates and experimental determinations in the presence of small amounts of fluid, but closely match calculated fractionations by means of the increment method for framework oxygen in tremolite. The small fractionations measured in the direct calcite-tremolite exchange experiments are interpreted by different rates of oxygen isotope exchange between hydroxyl oxygen, framework oxygen and calcite during the solid-solid reactions where significant recrystallization occurs. The three-phase system experiments were accomplished in the presence of a large amount of fluid (CO2+H2O) at 500 MPa and 560 °C under conditions of phase equilibrium for 5, 10, 20, 40, 80, 120, 160, and 200 days. The results show that oxygen isotope exchange between minerals and fluid proceeds in two stages: first, through a mechanism of dissolution-recrystallization and very rapidly; second, through a mechanism of diffusion and very slowly. Synthetic calcite shows a greater rate of isotopic exchange with fluid than natural calcite in the first stage. The rate of oxygen diffusion in calcite is approximately equal to or slightly greater than that in tremolite in the second stage. A calculation using available diffusion coefficients for calcite suggests that grain boundary diffusion, rather than volume diffusion, has been the dominant mechanism of oxygen transport between the fluid and the mineral grains in the later stage.